Kulish V. S., Niemtseva Ya. M. Verbal and non-verbal component of emotiveness in political discourse: translation aspect. - Kulish V. S.; Niemtseva Ya. M. (Philological Treatises, 2020)
The article deals with the question of creating the emotiveness in political message with verbal and non-verbal means. It points out the specific features of creative emotive effect by politicians. These features realize the high level of emotiveness in the communicants’ reaction. The paper is aimed at analyzing verbal and non-verbal component of emotiveness according to the translation aspect, ways of rendering emotions by means of different languages. The aim of the research implies conducting the detailed analysis of the conveyance of the linguistic and extralinguistic means of expressivity in the Ukrainian translations. As a result the features of emotions transmission on verbal and non-verbal levels were found, their functions in formation the emotive effect of a political message were determined and the ways of its rendering by means of correlated languages were distinguished.